Pemberdayaan Kreativitas Remaja Petukangan Utara Dalam Pembuatan Visual Konten Sosial Media Menggunakan Canva - Ahmad Pudoli; Irawan Irawan; Mardi Hardjianto; Purwanto Purwanto; Jan Everhard; Mohammad Syafrullah (Universitas Budi Luhur, 2026)
The rapid development of social media has significantly changed adolescents’ communication patterns and daily activities, yet it has not been fully matched by their ability to produce creative and useful visual content. Youth in Petukangan Utara are active social media users but mainly act as content consumers rather than creators. Based on this condition, this community service program aims to enhance youth creativity and digital skills through training in social media visual content creation using Canva. The method applied a participatory approach with a learning-by-doing model, including basic training, hands-on practice, mentoring, and group-based content production. The results show that around 85% of participants were able to operate Canva independently, 90% produced at least two visual designs, and 75% demonstrated improved understanding of basic visual communication principles. In addition, participants experienced increased confidence, creativity, and collaboration skills. The program also broadened participants’ awareness of using design skills to support social activities and MSME promotion. In conclusion, Canva-based training effectively improves youth digital skills and plays an important role in technology-based community empowerment